The Effect of Self-Management Education Based on the Health Promotion Model on Compliance Behavior of Hypertension Patients - Sakinah, Siti; Dee, Theodehild M.Theresia; Tusi , Juandri S. (Babali Nursing Research, 2024)
Introduction: Hypertension is a condition characterized by elevated blood pressure, in which an individual's blood pressure consistently remains above normal levels. Compliance with medication, adherence to dietary restrictions, and regular blood pressure monitoring are key components in the successful treatment of hypertensive patients. One approach to improving patient compliance in managing hypertension is the implementation of Self-Management Education (SME) based on the Health Promotion Model (HPM). This study aims to examine the effect of SME on compliance behavior among hypertensive patients in the Baumata Health Center, Kupang Regency. Method: A quasi-experimental design was used in this study, with 70 participants selected through purposive sampling, divided into two groups: 35 participants in the intervention group and 35 in the control group. The instruments used included the Morisky Medication Adherence Scale (MMAS-8), a hypertension diet questionnaire, and a blood pressure monitoring questionnaire. Data were analyzed using an independent t-test for bivariate analysis and MANOVA for multivariate analysis. Results: The findings indicate a significant effect of SME on the intervention group, with a p-value of < 0.05. The SME approach, based on HPM principles, involved patient empowerment and behavioral strategies. Ongoing support also contributed to sustained progress, leading to improved compliance in medication adherence, diet, and blood pressure monitoring among hypertensive patients. Conclusion: Future research should include larger sample sizes, more precise instruments, and longer study durations to achieve more robust results regarding compliance in hypertension management.